2008
DOI: 10.4161/cbt.7.9.6282
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of organic anion transporter polypeptide (OATP) genes in human breast carcinoma

Abstract: Organic anion transporter polypeptides (OATPs) mediate the transmembrane uptake of endogenous compounds and clinically important drugs in various tissues thereby effecting drug disposition and tissue penetration. OATPs have also been identified in gastric, pancreatic and colon carcinomas but little is known about their expression in breast carcinoma. We therefore analyzed the expression pattern of all 11 known OATPs in three breast cancer cell lines (MCF-7, ZR-75-1, MDA-MB-231) and one immortalized breast epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(101 citation statements)
references
References 17 publications
9
91
0
1
Order By: Relevance
“…Certain (60) ↑ in prostate cancer cells (6) qRT-PCR Kidney (64) ↑ in bone cancer (65) RT-PCR OATP1B1 Liver (2,66) ↓ in liver cancer (37)(38)(39)67,68) RT-PCR, IF, IB ↑ in colon polyps and colon cancer (63) RT-PCR ↑ in ovarian cancer (69) RT-PCR OATP1B3 Liver (3,70) ↓ in liver cancer (41) qRT-PCR, IB ↑ in colon cancer (4,71,72) RT-PCR, qRT-PCR, IB, IHC ↑ in pancreatic cancer (71)(72)(73) RT-PCR, qRT-PCR, IB, IHC ↑ in lung cancer (38) RT-PCR, qRT-PCR, IF ↑ in prostate cancer (16,17,68,74) qRT-PCR, IF ↑ in breast cancer (75) qRT-PCR, IHC ↑ in testicular cancer (68) qRT-PCR, IF ↑ in ovarian cancer (69) RT-PCR OATP1C1 Brain (76) ↑ in bone cancers (65) RT-PCR Testes (76) Ciliary body (77) OATP2A1 Ubiquitous (78) ↑ in breast cancer (79) qRT-PCR ↑ in liver cancer (80) qRT-PCR, IF ↑ in bone metastases from kidney cancer (65) qRT-PCR, IB ↓ in cancers of bowel, stomach, ovary, lung, and kidney (81) RT-PCR OATP2B1 Blood-brain barrier (82) ↑ in bone cancer (65) RT-PCR Heart (83) ↑ in breast cancers (79,84) qRT-PCR, IF, IB Enterocytes (85) ↓ in liver and pancreatic cancers (68) qRT-PCR Liver (86) Placenta (87) OATP3A1 Ubiquitous (88) ↑ in bone cysts …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain (60) ↑ in prostate cancer cells (6) qRT-PCR Kidney (64) ↑ in bone cancer (65) RT-PCR OATP1B1 Liver (2,66) ↓ in liver cancer (37)(38)(39)67,68) RT-PCR, IF, IB ↑ in colon polyps and colon cancer (63) RT-PCR ↑ in ovarian cancer (69) RT-PCR OATP1B3 Liver (3,70) ↓ in liver cancer (41) qRT-PCR, IB ↑ in colon cancer (4,71,72) RT-PCR, qRT-PCR, IB, IHC ↑ in pancreatic cancer (71)(72)(73) RT-PCR, qRT-PCR, IB, IHC ↑ in lung cancer (38) RT-PCR, qRT-PCR, IF ↑ in prostate cancer (16,17,68,74) qRT-PCR, IF ↑ in breast cancer (75) qRT-PCR, IHC ↑ in testicular cancer (68) qRT-PCR, IF ↑ in ovarian cancer (69) RT-PCR OATP1C1 Brain (76) ↑ in bone cancers (65) RT-PCR Testes (76) Ciliary body (77) OATP2A1 Ubiquitous (78) ↑ in breast cancer (79) qRT-PCR ↑ in liver cancer (80) qRT-PCR, IF ↑ in bone metastases from kidney cancer (65) qRT-PCR, IB ↓ in cancers of bowel, stomach, ovary, lung, and kidney (81) RT-PCR OATP2B1 Blood-brain barrier (82) ↑ in bone cancer (65) RT-PCR Heart (83) ↑ in breast cancers (79,84) qRT-PCR, IF, IB Enterocytes (85) ↓ in liver and pancreatic cancers (68) qRT-PCR Liver (86) Placenta (87) OATP3A1 Ubiquitous (88) ↑ in bone cysts …”
Section: Discussionmentioning
confidence: 99%
“…Similar to OATP3A1, OATP4A1 is also overexpressed in multiple cancer cell lines, aneurysmal bone cysts, liver cancers, and breast cancers (65,79,80,90). In colorectal neoplasia specimens, OATP4A1 mRNA levels were reported to be elevated (91).…”
Section: Oatp4a1 (Gene Symbol Slco4a1)mentioning
confidence: 99%
See 1 more Smart Citation
“…6), hepatocellular carcinomas (11), breast carcinomas (13), and lung cancer (12). In addition, expression of OATP1B1 and OATP1A2 was found in malignant breast cell lines (14,43), and OATP1A2 (and OATP2B1) have also been localized in the blood-tumor barrier of gliomas (44). Recently, Takano and colleagues (2009) have shown in vitro that hepatoma cells made resistant to paclitaxel treatment showed, besides increased P-glycoprotein expression, drastically decreased mRNA expression of SLCO1B3 (45).…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate readability and understanding of this manuscript, "OATP" is used for both genes and proteins. OATPs are expressed in a variety of tissues [15] and tumors [16,17], where they mediate the transport of endogenous and exogenous compounds, including drugs [12,13,18]. Studies have shown that uptake transporters can confer sensitivity to anticancer agents [19][20][21][22][23], such as the OATP1B3 substrate methotrexate [19].…”
Section: Introductionmentioning
confidence: 99%